2022
DOI: 10.1001/jamacardio.2022.3191
|View full text |Cite
|
Sign up to set email alerts
|

Measured Blood Pressure, Genetically Predicted Blood Pressure, and Cardiovascular Disease Risk in the UK Biobank

Abstract: ImportanceHypertension remains the major cardiovascular disease risk factor globally, but variability in measured blood pressure may result in suboptimal management. Whether genetic contributors to elevated blood pressure may complementarily inform cardiovascular disease risk assessment is unknown.ObjectiveTo examine incident cardiovascular disease by blood pressure polygenic risk score independent of measured blood pressures and antihypertensive medication prescriptions.Design, Setting, and ParticipantsThe co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Also, a UK Biobank study that included patients who reported antihypertensive use at baseline found SBP polygenic score was associated with uncontrolled BP (Odds ratio: 1.70; 95% CI: 1.6-1.8) 27 , top vs. bottom quintile. Another UK Biobank study testing cardiovascular associations with SBP polygenic score at baseline found high SBP increased the cardiovascular outcomes in untreated hypertension with 1.04-fold and in treated hypertension with 1.06-fold 44 . In our study, high SBP and DBP polygenic scores are associated with decrease the risk for discontinuation in patients with high polygenic score (HR SBP : 0.93, 0.88-0.99 and HR DBP : 0.93, 0.87-0.99, top vs. bottom quintile), and high polygenic scores of DBP decrease the risk of heart failure and coronary heart disease in people treated with dCCB (HR HF : 0.86, 0.74-0.99 and HR CHD : 0.91, 0.84-0.99, top vs. bottom quintile) suggesting that those with the most severely increased blood pressures are more likely to continue treatment compared to those with more moderately increased pressures (although we lack data to test this directly).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a UK Biobank study that included patients who reported antihypertensive use at baseline found SBP polygenic score was associated with uncontrolled BP (Odds ratio: 1.70; 95% CI: 1.6-1.8) 27 , top vs. bottom quintile. Another UK Biobank study testing cardiovascular associations with SBP polygenic score at baseline found high SBP increased the cardiovascular outcomes in untreated hypertension with 1.04-fold and in treated hypertension with 1.06-fold 44 . In our study, high SBP and DBP polygenic scores are associated with decrease the risk for discontinuation in patients with high polygenic score (HR SBP : 0.93, 0.88-0.99 and HR DBP : 0.93, 0.87-0.99, top vs. bottom quintile), and high polygenic scores of DBP decrease the risk of heart failure and coronary heart disease in people treated with dCCB (HR HF : 0.86, 0.74-0.99 and HR CHD : 0.91, 0.84-0.99, top vs. bottom quintile) suggesting that those with the most severely increased blood pressures are more likely to continue treatment compared to those with more moderately increased pressures (although we lack data to test this directly).…”
Section: Discussionmentioning
confidence: 99%
“…For younger individuals, polygenic risk scores may be helpful in identifying high-risk individuals meriting antihypertensives earlier. 11 This study by Clarke and colleagues also provides important insights regarding the influence of sex on the EDITORIAL cardiovascular risk associated with SBP. Observational studies have yielded conflicting results as to whether men and women have the same cardiovascular risk for a given SBP range with uncertainty over residual confounding.…”
Section: See Related Article Pp 566-576mentioning
confidence: 93%
“…For younger individuals, polygenic risk scores may be helpful in identifying high-risk individuals meriting antihypertensives earlier. 11…”
mentioning
confidence: 99%
“…PGSs combine the effect of many genetic variants on a phenotype, which can either be qualitative (e.g., disease status) or quantitative (e.g., blood biomarker level). While ethical and societal implications need careful consideration before widespread deployment 17,18 , PGSs are increasingly being considered for their clinical utility, e.g., in the context of precision medicine 17,[19][20][21][22][23] . Numerous methods exist for computing trait and disease PGSs on individual-level data [24][25][26][27][28] and summary statistics [29][30][31][32][33][34] , but they generally only model additive relationships between genotype and target.…”
Section: Introductionmentioning
confidence: 99%